Social psychology and the concept of culture - Noriega, José Ángel Vera (2011)
The objective of this critic review related to the cultural concept is to review the contemporary theories of the social psychology; taking in count its experimental designs and data, and its way to assume, to measure and to evaluate the cultural concept. There were analyzed the theories: individualism-collectivism, social capital, social and ethnic identity as well as the concentric and adaptative systems. Both of them there were analyzed from the theorical perspective of culture (sociological-anthropological construct) as a non-psychological category that integrates the social aspects linked to the formation of values and to the representations which transversally cut the social behavior.